A comparative efficacy study of diagnostic digital breast tomosynthesis and digital mammography in BI-RADS 4 breast cancer diagnosis. Issue 153 (August 2022) - Ezeana, Chika F.; Puppala, Mamta; Wang, Lin; Chang, Jenny C.; Wong, Stephen T.C.
Highlights: We evaluated clinical performance of DBT vs. 2D among diagnostic BI-RADS4 cases. BI-RADS4 cohorts considered in toto as no available data on 4a, 4b and 4c subclasses. DBT cases significantly assessed as BI-RADS4 5.66% more often than 2D cases. DBT not significantly better in CDR (120.76 vs. 112.65) and PPV3 (15.99 vs. 14.41) DBT not better sensitivity in BI-RADS4; adjusted odds-ratio: 1.04 (CDR), 1.09 (PPV3) Abstract: Purpose: Probability of malignancy for BI-RADS 4-designated breast lesions ranges from 2% to 95%, contributing to high false-positive biopsy rates. We compare clinical performance of digital breast tomosynthesis (DBT) versus digital mammography (2D) among our BI-RADS 4 population without prior history of breast cancer. Methods: We extracted retrospective data i.e., clinical, mammogram reports, and biopsy data, from electronic medical records across Houston Methodist's nine hospitals for patients who underwent diagnostic examinations using both modalities (02/01/2015 – 09/30/2020). 2D and DBT cohorts were not intra-individual matched, and there was no direct mammogram evaluation. Using Student's t test, Fisher's exact test, and Chi-squared test, we evaluated the data to determine statistical significance of differences between modalities in BI-RADS 4 cases. We calculated adjusted odds-ratio between modalities for cancer detection rate (CDR) and biopsy-derived positive predictive value (PPV3). Results: There were 6, 356 encounters (6, 020 patients) in 2D and 5, 896 encounters (5, 637 patients) in DBT assessed as BI-RADS 4. Using Fisher's exact test, DBT mammography cases were significantly assessed as BI-RADS 4 5.66% more often than those undergoing 2D mammography, P = 0.0046 (1.0566 95% CI: 1.0169–1.0977). The CDRs were 112.65 (2D) and 120.76 (DBT), adjusted odds-ratio: 1.04 (0.93, 1.16)), P = 0.5029, while PPV3 were 14.41% (2D) and 15.99% (DBT), adjusted odds-ratio: 1.09 (0.97, 1.22), P = 0.1483 ; both logistic regression-adjusted for all other factors. Conclusion: DBT did not achieve better performance and sensitivity in assigning BI-RADS 4 cases compared with 2D, showed no significant advantage in CDR and PPV3, and does not reduce false-positive biopsies among BI-RADS 4-assessed patients.